Soft magnetic material
Patent Information
- Application Number
- JP2023141959
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-01
- Publication Date
- 2025-03-13
AI Technical Summary
【0012】 上記[1]の構成を有する本発明にかかる軟磁性材料は、Coの含有により、高い飽和磁束密度を有する。一方で、Coの含有量が比較的少量に抑えられていることで、規則相の生成による脆化を抑制することができる。Coの含有量の低減により、コアロスが大きくなりやすいが、SiおよびAlの含有により、軟磁性材料のコアロスを低く抑えることができる。
Smart Images

Figure 2025035126000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a soft magnetic material, and more particularly to a soft magnetic material that can be suitably used to form a motor core material or the like. [Background technology]
[0002] In recent years, with the spread of new types of mobile devices such as electric cars and drones, there is an increasing demand for motors with higher output and smaller size than before to drive these mobile devices. In order to achieve high output and miniaturization of motors, soft magnetic materials with high saturation magnetic flux density are required as core materials. One method for increasing the saturation magnetic flux density of soft magnetic materials is the addition of Co. An example of a soft magnetic material with increased saturation magnetic flux density by containing a large amount of Co is Fe-49Co-2V material (Permendur).
[0003] However, when a soft magnetic material contains a large amount of Co, such as permendur, the large amount of Co generates an embrittled phase (ordered phase), which reduces the workability of the material. In addition, Co is an expensive element, and the increase in material costs due to the inclusion of a large amount of Co is also a problem. In order to suppress the decrease in workability and the increase in material costs, attempts have been made to reduce the Co content, but this tends to increase core loss (iron loss) in the soft magnetic material. In order to suppress the core loss, it is effective to add Si or Al to the soft magnetic material. Soft magnetic materials in which Si and Al are added while keeping the Co content to a relatively small amount are disclosed, for example, in the following Patent Documents 1 and 2. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Special Publication No. 2004-515644 [Patent Document 2] JP 2017-2395 A Summary of the Invention
Problems to be Solved by the Invention
[0005] As described above, when the addition amount of Co in the Fe-Co-based soft magnetic material is relatively small, adding Si or Al is effective in reducing core loss. However, even if the addition amounts of Si and Al are increased, there is a limit to the improvement of the core loss reduction effect, and adding a large amount of Si or Al may cause other problems such as deterioration of toughness. Thus, it is difficult to obtain a material that兼备 both a high saturation magnetic flux density and a low core loss by adjusting the component composition of the soft magnetic material. However, for applications such as core materials that contribute to higher output and smaller size of motors, the development of soft magnetic materials having兼备 these characteristics is desired.
[0006] The problem to be solved by the present invention is to provide a soft magnetic material having a high saturation magnetic flux density and a low core loss.
Means for Solving the Problems
[0007] To solve the above problems, the soft magnetic material of the present invention has the following configuration.
[0008] [1] The soft magnetic material of the present invention is configured as a rolled material of an alloy containing, by mass%, 10% < Co ≤ 20%, 0.1% ≤ Si ≤ 2.0%, 0.1% ≤ Al ≤ 2.0%, with the balance being Fe and unavoidable impurities. On the rolled surface after magnetic annealing, the value of A obtained by the following formulas (1) and (2) is less than 32°, and the area ratio of the region having a crystal orientation within 10° from the {411}<148> orientation is less than 20%.
Equation
[0009] [2] In the aspect of [1] above, it is preferable that the content of each element contained as the inevitable impurity is suppressed to the following range in mass%. C ≦ 0.020%, Mn ≦ 0.10%, P ≦ 0.010%, S ≦ 0.005%, Cu ≦ 0.05%, Ni ≦ 0.10%, Cr ≦ 0.10%, Mo ≦ 0.10%, Ti ≦ 0.010%, O ≦ 0.005%, N ≦ 0.005%.
[0010] [3] In the aspect of [1] above, it is preferable that the soft magnetic material further contains at least one of 0% < V ≦ 2.0% and 0% < Cr ≦ 2.0% in mass%.
[0011] [4] In any one of the aspects of [1] to [3] above, it is preferable that the crystal grain size on the rolled surface after magnetic annealing is 30 μm or more and 100 μm or less.
Advantages of the Invention
[0012] The soft magnetic material according to the present invention having the configuration of [1] above has a high saturation magnetic flux density due to the inclusion of Co. On the other hand, since the content of Co is suppressed to a relatively small amount, embrittlement due to the formation of a regular phase can be suppressed. Although the core loss tends to increase due to a reduction in the content of Co, the core loss of the soft magnetic material can be kept low by the inclusion of Si and Al.
[0013] In this way, the soft magnetic material of the present invention can achieve high saturation magnetic flux density and low core loss as a result of the composition of the components, but when the soft magnetic material has a specific crystal orientation, the soft magnetic properties are improved and the core loss is further reduced. First, the smaller the A value obtained by the above formulas (1) and (2), the more the magnetic flux density is in the direction within the rolling plane or close to it. <100> This shows that many crystal grains with orientation are formed, but the value of A is less than 32°, which is the easy axis of magnetization. <100> By accumulating a sufficient number of crystal grains whose orientation is in the rolling plane or close to it, high soft magnetic properties can be obtained when a magnetic field is applied in the rolling plane. <148> Oriented grains impair the soft magnetic properties, but the {411} orientation on the rolled surface <148> By suppressing the area ratio of oriented grains (area ratio of regions with a crystal orientation within 10° of the desired orientation) to less than 20%, the soft magnetic properties are maintained at a high level. In this way, the soft magnetic material has a specified crystal orientation state, and the soft magnetic properties are improved, thereby reducing hysteresis loss and eddy current loss, and keeping the core loss small overall. A value and {411} <148> The area ratio of oriented grains can be controlled by the hot rolling and cold rolling conditions when producing the soft magnetic material as a rolled material, in particular the hot rolling temperature and the reduction rate during cold rolling.
[0014] In the above aspect [2], the content of each element contained as an unavoidable impurity is controlled within the above range, thereby minimizing the effect of the unavoidable impurities on the magnetic properties of the soft magnetic material.
[0015] In the above aspect [3], the soft magnetic material contains V, which improves the processability of the soft magnetic material. Also, the soft magnetic material contains Cr, which improves the electrical resistance and corrosion resistance of the soft magnetic material. The V and Cr contents are kept below the upper limits, which minimizes the effect of the inclusion of these elements on the magnetic properties of the soft magnetic material.
[0016] In the above aspect [4], the grain size on the rolled surface after magnetic annealing is 30 μm or more, so that the generation of oriented grains that adversely affect the soft magnetic properties of the soft magnetic material is suppressed at the grain boundaries. This makes it easier to keep the value of A small and ensure high soft magnetic properties. On the other hand, by keeping the grain size to 100 μm or less, the toughness of the soft magnetic material can be improved. [Brief description of the drawings]
[0017] [Figure 1] FIG. 2 is a diagram showing a schematic distribution of crystal grain orientations on a rolled surface of a soft magnetic material according to one embodiment of the present invention. [Diagram 2] 1 shows ODF diagrams (φ2=45°) for (a) Example A3 and (b) Comparative Example A1. [Diagram 3] For (a) Example C2 and (b) Comparative Example C2, the IPF maps show {411} <148> FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] A soft magnetic material according to one embodiment of the present invention will be described in detail below. The soft magnetic material according to this embodiment is formed as a rolled material of an alloy having a predetermined component composition, and has a predetermined crystal orientation state. In this specification, the content of each element is shown in mass%. In addition, various properties are values measured in air at room temperature.
[0019] [Component composition of soft magnetic materials] A soft magnetic material according to one embodiment of the present invention contains the following prescribed amounts of Co, Si, and Al, with the remainder being unavoidable impurities and Fe.
[0020] 10% <Co≦20% In Fe-Co alloys, Co improves the soft magnetic properties of the material, including enhancing the saturation magnetic flux density (saturation magnetization). In the soft magnetic material according to this embodiment, by setting the Co content to 10% < Co, a sufficiently high saturation magnetic flux density can be obtained. It is more preferable that 12% ≦ Co and 15% ≦ Co.
[0021] However, if too much Co is contained in the soft magnetic material, a brittle phase (regular phase) is generated, causing the material to become brittle and reducing its workability. Also, Co is an expensive element, and adding a large amount leads to an increase in material cost. To suppress these situations, in the soft magnetic material according to this embodiment, the Co content is suppressed to Co ≦ 20%. It is more preferable that Co ≦ 19%.
[0022] ·0.1% ≦ Si ≦ 2.0% In the soft magnetic material, Si reduces the magnetocrystalline anisotropy constant and the magnetostriction constant, thereby contributing to the reduction of core loss. In the soft magnetic material according to this embodiment, since the Co content is suppressed to 20% or less, the effect of improving the saturation magnetic flux density by Co is suppressed to a certain level, which contributes to increasing the core loss. However, by containing Si, the increase in core loss in the soft magnetic material can be suppressed. Since the Si content in the soft magnetic material is 0.1% ≦ Si, the effect of reducing core loss can be fully obtained. It is more preferable that 0.3% ≦ Si and 0.5% ≦ Si.
[0023] On the other hand, if too much Si is contained in the soft magnetic material, it causes a decrease in the saturation magnetic flux density and deterioration of toughness. From the perspective of suppressing these situations, the Si content is set to Si ≦ 2.0%. It is more preferable that Si ≦ 1.5%.
[0024] ·0.1% ≦ Al ≦ 2.0% Similar to Si, Al also reduces the core loss of soft magnetic materials by reducing the crystal magnetic anisotropy constant and the magnetostriction constant. The content of Al in the soft magnetic material is 0.1% ≤ Al, so that the effect can be obtained sufficiently. 0.3% ≤ Al and 0.5% ≤ Al are more preferable.
[0025] On the other hand, if too much Al is contained in the soft magnetic material, it will cause a decrease in the saturation magnetic flux density and a deterioration in toughness, similar to Si. From the viewpoint of suppressing these situations, the content of Al is set to Al ≤ 2.0%. Al ≤ 1.5% is more preferable.
[0026] The soft magnetic material according to this embodiment has both a high saturation magnetic flux density and a low core loss by containing the above-mentioned predetermined amounts of Co, Si, and Al. In addition to the above-mentioned predetermined amounts of Co, Si, and Al which are essential components, the soft magnetic material may optionally contain at least one of the following predetermined amounts of V and Cr.
[0027] · 0% < V ≤ 2.0% By adding V to the soft magnetic material, the workability of the soft magnetic material can be improved. Since V shows the effect of improving workability even in a small amount, the lower limit of the content of V is not particularly defined. Preferably, 0.10% < V. On the other hand, from the viewpoint of suppressing the influence on the magnetic properties of the soft magnetic material, the content of V is suppressed to V ≤ 2.0%.
[0028] · 0% < Cr ≤ 2.0% By adding Cr to the soft magnetic material, the electrical resistance of the soft magnetic material can be improved and the corrosion resistance can be enhanced. The improvement of the electrical resistance leads to the reduction of the core loss. Since Cr exhibits these effects even in a small amount, the lower limit of the content of Cr is not particularly defined. Preferably, 0.10% < Cr. On the other hand, from the viewpoint of suppressing the influence on the magnetic properties of the soft magnetic material, the content of Cr is suppressed to Cr ≤ 2.0%. Note that a very small amount of Cr of Cr ≤ 0.10% can be regarded as an unavoidable impurity.
[0029] In the soft magnetic material according to the present embodiment, the inclusion of unavoidable impurities is permitted within a range that does not significantly impair the magnetic properties of the soft magnetic material. Specific examples of unavoidable impurities include C≦0.020%, Mn≦0.10%, P≦0.010%, S≦0.005%, Cu≦0.05%, Ni≦0.10%, Cr≦0.10%, Mo≦0.10%, Ti≦0.010%, O≦0.005%, and N≦0.005%. If the content of each element is suppressed within the above range, the inclusion of those elements is unlikely to significantly affect the magnetic properties of the soft magnetic material. By allowing the inclusion of impurities within the above content range, it is possible to avoid an increase in manufacturing costs due to excessive elimination of the inclusion of impurities in the manufacturing of the soft magnetic material.
[0030] [Method of manufacturing soft magnetic materials] Before describing the crystal orientation state of the soft magnetic material, a manufacturing method of the soft magnetic material will be briefly described. The soft magnetic material according to this embodiment can be suitably manufactured by melting and casting, followed by hot rolling, annealing as necessary, cold rolling, and further magnetic annealing.
[0031] In the soft magnetic material according to the present embodiment, the hot rolling temperature during hot rolling and the rolling reduction during cold rolling have a large effect on the crystal orientation state of the resulting soft magnetic material. As will be described in detail later, the crystal orientation state can be controlled by selecting the hot rolling temperature and the rolling reduction rate during cold rolling. The hot rolling temperature needs to be higher than 970°C in order to obtain a predetermined crystal orientation state, which will be described later.
[0032] Annealing after hot rolling may be performed under conditions that can sufficiently remove processing strain, and examples of such conditions include heating and holding at a temperature in the range of 700°C to 900°C. In addition, after cold rolling, a magnetic annealing process is performed to uniformly coarse the crystal grains, thereby reducing the core loss of the soft magnetic material. For example, the soft magnetic material may be held at a temperature in the range of 850°C to 950°C in a vacuum or in a non-oxidizing atmosphere such as ammonia decomposition gas. The crystal grain size in the soft magnetic material can be finally adjusted by the heating temperature during magnetic annealing.
[0033] [Crystal orientation of soft magnetic materials] Next, the crystal orientation state of the soft magnetic material of this embodiment will be described. The soft magnetic material according to this embodiment, which is configured as a rolled material, has the following crystal orientation state (crystal structure) on the rolled surface. In the following, the crystal orientation state of the soft magnetic material is defined for the state after hot rolling, cold rolling, and magnetic annealing. Magnetic annealing for evaluating the crystal orientation state may be performed at a temperature of 850 to 950°C, for example, 950°C as in the following example.
[0034] In the soft magnetic material according to this embodiment, the value of A (A parameter) defined by the following formulas (1) and (2) is less than 32° on the rolled surface.
number
[0035] The A parameter is the <100> This parameter indicates how close the orientation is to the rolling surface, on average. The smaller the A parameter, the more likely it is to be in the rolling surface or close to it. <100> It indicates that oriented crystal grains occupy much of the rolled surface. The A parameter was proposed by Kestens et al. (L. Kestens and S. Jacobs, "Texture Control During the Manufacturing of Nonoriented Electrical Steels", Texture, Stress, and Microstructure 2008 (2008), ID 173083), and can be estimated from the orientation distribution function (ODF) obtained by electron backscatter diffraction (EBSD) measurement of soft magnetic materials.
[0036] As shown in Figure 1, in a rolled material, many crystal grains exist on the rolled surface defined by the rolling direction (RD) and the transverse direction (TD) perpendicular to it. As shown in the figure, each crystal grain is composed of cubic crystals of an Fe-Co alloy, and the crystal orientation of these crystal grains is as shown in the figure. <100> As the orientation is shown by the arrows, the direction can be in various directions. In a crystal grain having a certain crystal orientation g, there is an arbitrary magnetization direction θ (for example, TD) and three equivalent <100> Closest in direction <100> The minimum angle between the direction is A in equation (1). θ f(g) is the orientation distribution function (ODF), and in equation (1), A θ By taking the convolution of (g) and f(g), A θ As the magnetization direction θ and the grain <100> The weighted average of the angular differences from the direction (average angular difference) is calculated.
[0037] When soft magnetic materials are used as components of rotating electrical machines, such as the core material of motors, the magnetization direction is uniformly distributed within the rolled surface, so θ can take any angle within the rolled surface. θThe A parameter is obtained by integrating in all directions in the rolling plane. The A parameter is the <100> The weighted average of the angle of inclination of the grains relative to the rolling surface is used to measure the EBSD. <100> Measure the angle difference of the direction, A θ (g) and A obtained at all measurement points θ (g) is added and averaged to get A θ You can get that A θ We can calculate the value of A by integrating with respect to θ.
[0038] As mentioned above, the smaller the value of the A parameter, the closer the magnetization axis of each crystal grain is to the magnetization axis. <100> It is shown that the orientation is oriented in a direction close to the rolled surface on average, and when a magnetic field is applied in any direction in the rolled surface, the soft magnetic material exhibits high soft magnetic properties. The soft magnetic material according to this embodiment exhibits excellent soft magnetic properties and is highly effective in reducing core loss because the A parameter is less than 32°. It is more preferable that the A parameter is 30° or less, and more preferably 29° or less. The smaller the A parameter, the more preferable, and the lower limit is not particularly limited, but the A parameter that can be obtained in reality is generally 20° or more.
[0039] The A parameter can be controlled by the hot rolling temperature during hot rolling and the reduction rate during cold rolling in the manufacturing process of soft magnetic materials. The higher the hot rolling temperature, the smaller the grain boundaries are, and the less favorable orientation grains from a soft magnetic standpoint develop from the grain boundaries, resulting in a relatively smaller grain size within the rolled surface. <100> The ratio of oriented grains can be increased. In this embodiment, by setting the hot rolling temperature to a temperature higher than 970°C, it becomes easier to suppress the A parameter to less than 32°. More preferably, the hot rolling temperature is set to 1000°C or higher, or 1050°C or higher. From the viewpoint of suppressing the A parameter to a small value, no particular upper limit is set for the hot rolling temperature, but a temperature of approximately 1500°C or lower is sufficient. For example, when the hot rolling temperature is lowered to 900°C or lower, it is difficult to suppress the A parameter to a small value such as less than 32°.
[0040] Regarding the reduction ratio during cold rolling, the higher the reduction ratio, the more the grains <100> The orientation is easily oriented in the rolled surface, and the A parameter tends to be small. As shown in the examples below, the lower limit of the reduction ratio that gives an A parameter of less than 32° also depends on the component composition of the soft magnetic material, but the reduction ratio can be set according to the component composition so that the A parameter can be sufficiently kept small. For example, when the Si content is less than 1.0%, if the reduction ratio is 90% or more, the A parameter can be kept less than 32° in a wide range of component compositions. From the viewpoint of reducing the A parameter, the higher the reduction ratio, the more preferable, and no upper limit is particularly set.
[0041] Furthermore, the crystal orientation of the soft magnetic material according to this embodiment is {411} on the rolled surface. <148> The area ratio of the oriented grains is less than 20%. In this specification, in the evaluation of the area ratio of a specific oriented grain, the measurement tolerance angle difference is 10° or less. <148> The area ratio of oriented grains is {411} <148> This refers to the area ratio of the region with a crystal orientation within 10° of the orientation. {411} <148> The area ratio of oriented grains can be estimated from the inverse pole figure orientation map (IPF map) obtained by EBSD.
[0042] As shown in the following examples, the present inventors have found that {411} <148> It was found that the occurrence of many oriented grains on the rolled surface increases the core loss of soft magnetic materials. <148> It is believed that the orientation of the grains impairs the soft magnetic properties of the soft magnetic material. <148> The area ratio of oriented grains is less than 20%, which keeps core loss to a minimum. {411} <148> The area ratio of oriented grains is preferably 18% or less, more preferably 10% or less. <148> The smaller the area ratio of oriented grains, the more preferable it is, and as shown in the examples, it can be reduced to 0%.
[0043] {411} <148> The area ratio of the oriented grains can also be controlled by the hot rolling temperature during hot rolling and the reduction ratio during cold rolling. The area ratio is particularly dependent on the reduction ratio during cold rolling. The lower the reduction ratio, the smaller the area ratio. As shown in the following examples, the upper limit of the reduction ratio that gives an area ratio of less than 20% also depends on the component composition of the soft magnetic material, but the reduction ratio may be set according to the component composition so that the area ratio can be sufficiently kept small. For example, when the Si content is less than 1.0%, if the reduction ratio is less than 95%, the area ratio can be kept less than 20% in a wide range of component compositions. From the viewpoint of reducing the area ratio, the lower the reduction ratio, the more preferable, and no lower limit is set. As described above, the higher the reduction ratio, the smaller the A parameter becomes, so the lower limit of the cold rolling reduction ratio is set so that the A parameter is less than 32°, and the {411} <148> The upper limit of the rolling reduction rate may be determined so that the area ratio of oriented grains is less than 20%.
[0044] As described above, the soft magnetic material according to the present embodiment has an A parameter of less than 32° and a {411} <148> The area ratio of oriented grains is less than 20%, which results in excellent soft magnetic properties and reduced core loss. Core loss (iron loss) includes the contributions of hysteresis loss and eddy current loss, and is due to the reduction of the A parameter and the {411} <148> The reduction in the area ratio of oriented grains and the reduction in the hysteresis loss and the eddy current loss can contribute to the reduction of each of them. In particular, the reduction in the area ratio of oriented grains and the reduction in the area ratio of oriented grains can contribute to the reduction of the hysteresis loss and the eddy current loss. <148> The effect of reducing hysteresis loss by reducing the area ratio of oriented grains becomes significant.
[0045] Furthermore, in the soft magnetic material according to this embodiment, the crystal grain size is preferably 30 μm or more and 100 μm or less as the state of the structure of the rolled surface. If the crystal grain size is 30 μm or more, the proportion of the crystal grain boundaries in the rolled surface is small, and the generation of oriented grains that occur at the crystal grain boundaries and have a negative effect on the soft magnetic properties can be suppressed. As a result, the value of the A parameter can be kept small to ensure high soft magnetic properties, and the effect of reducing core loss can be enhanced. It is more preferable that the crystal grain size is 40 μm or more, or 50 μm or more. On the other hand, if the crystal grain size is 100 μm or less, the toughness of the soft magnetic material can be improved due to the effect of fine crystal grains. It is more preferable that the crystal grain size is 90 μm or less, or 80 μm or less. The crystal grain size depends on the conditions of magnetic annealing as well as the conditions of hot rolling and cold rolling, and the crystal grain size becomes smaller as the reduction ratio during cold rolling is increased. Generally, when the A parameter is less than 32° and the {411} <148> If the rolling reduction rate is determined so that the area ratio of oriented grains is less than 20%, a crystal grain size of 30 μm or more and 100 μm or less can be obtained.
[0046] [Characteristics of soft magnetic materials] As described above, the soft magnetic material according to the present embodiment has a predetermined component composition, and thus has both a high saturation magnetic flux density and a low core loss. <148> By adopting a crystal orientation state in which the area ratio of oriented grains is suppressed to a small value, the soft magnetic properties are improved, and the effect of suppressing core loss to a low level is enhanced. The soft magnetic material according to this embodiment has a high saturation magnetic flux density and a low core loss, and can be suitably used as a component of a rotating electric machine, such as a core material for a motor. In particular, it is suitable for increasing the output and miniaturizing the motor.
[0047] The soft magnetic material according to this embodiment has the above-mentioned component composition and crystal orientation state, and thus can obtain a saturation magnetic flux density (saturation magnetization) of 2.1 T or even a large value exceeding 2.2 T. Furthermore, the core loss can be suppressed to less than 200 W / kg as measured at an excitation magnetic flux density of 1.5 T and a frequency of 1 kHz. By adjusting the component composition, such as by setting the Si content to 1.0% or more, or by making the rolling reduction rate relatively high, the core loss can be further suppressed to less than 195 W / kg or less than 190 W / kg. EXAMPLES
[0048] The present invention will be described in more detail below using examples, but the present invention is not limited to these examples.
[0049] [Sample preparation] As a number of examples and comparative examples, soft magnetic materials having the composition shown in Tables 1 to 5 (containing Co, Si, and Al in the mass% concentrations shown, with the remainder consisting of unavoidable impurities and Fe) were produced through hot rolling at the temperatures shown and cold rolling at the rolling reductions shown. As a specific manufacturing method, metal materials having each composition ratio were melted in a vacuum induction furnace and cast. The obtained ingots were hot rolled at each hot rolling temperature shown in the table. The obtained plate material was descaled and then annealed at 750°C for 6 hours. Furthermore, cold rolling was performed at the rolling reductions shown to obtain plate materials with a thickness of 0.2 mm. Finally, magnetic annealing was performed at 950°C for 4 minutes in an ammonia decomposition gas atmosphere to obtain soft magnetic materials according to each example and comparative example. In each soft magnetic material, the content of each element contained as an unavoidable impurity was in the following ranges: C≦0.020%, Mn≦0.10%, P≦0.010%, S≦0.005%, Cu≦0.05%, Ni≦0.10%, Cr≦0.10%, Mo≦0.10%, Ti≦0.010%, O≦0.005%, N≦0.005%.
[0050] [Test Method] The soft magnetic materials obtained through the above steps were subjected to the following evaluations. Unless otherwise specified, the evaluations were performed at room temperature in the air.
[0051] (1) Crystal orientation EBSD measurements were performed on the rolled surface of each soft magnetic material in a vacuum. Based on the results of the EBSD measurements, the A parameter was calculated using the above formulas (1) and (2). In addition, the IPF map obtained by the EBSD measurements showed that the {411} <148> The area ratio of oriented grains was evaluated. The measurement allowable angle difference was 10°. The measurement field of view was 1000 μm × 1000 μm.
[0052] (2) Crystal grain size For the test pieces cut out from each soft magnetic material, the surface was observed under an optical microscope, and the average grain size of the structure was determined and taken as the crystal grain size.
[0053] (3) Saturation magnetization For each soft magnetic material, the saturation magnetization (Js) was recorded using a vibrating sample magnetometer (VSM) as the value of magnetization at a magnetic field strength of 2000 kA / m.
[0054] (4) Core loss The soft magnetic material of each sample was processed into a circular shape, and five sheets were stacked together to create a circular laminated core with an outer diameter of 28 mm, an inner diameter of 20 mm, and a thickness of 1 mm. Using this laminated core, a primary winding of 100 turns and a secondary winding of 100 turns were provided to create a measurement sample. The core loss was then measured using a core loss measuring device. At this time, a sinusoidal AC magnetic field with an excitation magnetic flux density of 1.5 T and a frequency of 1 kHz was generated by the primary winding, and the core loss was evaluated based on the voltage induced in the secondary winding. Furthermore, the core loss (P cv ) and hysteresis loss (P h ) and eddy current loss (P e This separation is done by dividing the contribution of the core loss (P cv ) divided by frequency (f) (P cv This was based on the frequency dependence of P cvThe value obtained by extrapolating / f to 0 Hz is the hysteresis loss coefficient per cycle (K h =P h / f), which gives the hysteresis loss P h was calculated.
number
[0055] [Test Results] Tables 1 to 5 show the results of each evaluation for each example and comparative example, along with the composition, hot rolling temperature, and cold rolling reduction. FIG. 2 shows the ODF diagrams obtained by EBSD for (a) Example A3 and (b) Comparative Example A1 as representative examples. FIG. 3 shows the IPF maps obtained by EBSD for (a) Example C2 and (b) Comparative Example C2 as representative examples. {411} <148> The grain orientation is shown in color.
[0056] [Table 1]
[0057] [Table 2]
[0058] [Table 3]
[0059] [Table 4]
[0060] [Table 5]
[0061] According to Tables 1 to 4, for each example where the soft magnetic material contains 10% < Co ≤ 20%, 0.1% ≤ Si ≤ 2.0%, 0.1% ≤ Al ≤ 2.0%, the A parameter is less than 32°, and the area ratio of {411}<148> oriented grains is less than 20%, in each case, a large saturation magnetization exceeding 2.1 T can be obtained, and the core loss (P cv ) is suppressed to a low level of less than 200 W / kg. The saturation magnetization is mainly determined according to the Co content. On the other hand, the core loss also depends on the Si content, the A parameter, and the area ratio of {411}<148> oriented grains. In Example Groups C and D with a large Si content, they are suppressed to particularly low levels of 195 W / kg or less and less than 190 W / kg, respectively.
[0062] Furthermore, in each example, the crystal grain size is within the range of 30 μm or more and 100 μm or less. The crystal grain size being 100 μm or less indicates that the soft magnetic material has good toughness.
[0063] In contrast, each comparative example does not have any of the predetermined component compositions, an A parameter less than 32°, or an area ratio of {411}<148> oriented grains less than 20%. Correspondingly, in each comparative example, at least one of a saturation magnetization exceeding 2.1 T and a sufficiently reduced core loss is not obtained. In Comparative Examples E1 to E3 in Table 5, corresponding to the low Co content of 10% or less, the saturation magnetization is 2.1 T or less. On the other hand, in Comparative Examples E4 and E5, since the Co content exceeds 20%, the saturation magnetization is large, but the core loss is as large as 200 W / kg or more. In these Comparative Examples E4 and E5, the area ratio of {411}<148> oriented grains also exceeds 20%.
[0064] Even though they have a predetermined composition, the A parameter is 32° or more in Comparative Examples A1, A2, B1, B2, B4, B5, C1, C4 to C6, and D1, and the {411} <148> The area ratio of oriented grains is 20% or more. In these comparative examples, the core loss is higher than that of each example having the same component composition. Specifically, the core loss is 200 W / kg or more in comparative examples A and B, 195 W / kg or more in comparative example C, and 190 W / kg or more in comparative example D. For comparative examples A1, A3, B1, B2, B3, C1, and D1, the crystal grain size is also outside the range of 30 μm or more and 100 μm or less.
[0065] where A parameter and {411} <148> The relationship between the area ratio of oriented grains and the manufacturing conditions of soft magnetic materials will be examined. In Tables 2 and 3, the hot rolling temperature is changed for the same composition. According to these, when the hot rolling temperature exceeds 970°C, the cold rolling reduction is sufficiently increased as in Examples B1 to B6 and C1 to C5, so that the A parameter can be made less than 32°. In contrast, in Comparative Examples B4, B5, and C4 to C6, where the hot rolling temperature is 970°C or less, the A parameter is 32° or more. From this, it can be seen that in order to suppress the A parameter to less than 32°, the hot rolling temperature needs to be higher than 970°C.
[0066] In Tables 1 to 4, the reduction ratio during cold rolling is changed when the hot rolling temperature is 1100°C. From these data, it can be seen that the A parameter tends to become smaller as the reduction ratio increases. In the ODF diagram of FIG. 2 shown as a representative example, (a) Example A3 and (b) Comparative Example A1 have different reduction ratios, and it is confirmed that in Example A3, which has a higher reduction ratio, the contour lines are concentrated near the upper edge of the diagram corresponding to the crystal orientation in which the {100} plane faces the rolled surface, and the rolled surface contains many crystal grains in which the {100} plane faces. In Comparative Example A1, which has a low reduction ratio, the contour lines are distributed over a wide area in the diagram, and the crystal structure is close to a random orientation. On the other hand, the {411} <148> The area ratio of oriented grains tends to increase as the reduction ratio increases. In Fig. 3, which is a representative example, the area ratio of oriented grains is larger in (a) Example C2 and (b) Comparative Example C2, which have different reduction ratios. <148> It can be seen that the area occupied by the grains with the {411} orientation is significantly smaller. From these results, it can be seen that by setting the upper and lower limits of the rolling reduction, the A parameter of less than 32° and the {411} orientation of less than 20% can be suppressed. <148> The data in Tables 1 to 4 show that the A parameter and {411} <148> The reduction in the area ratio of oriented grains reduces the hysteresis loss (P h ) and eddy current loss (P e ) and the overall core loss (P cv ), especially in the case of <148> Reduction in the area ratio of oriented grains and hysteresis loss (P h ) reduction is strongly correlated.
[0067] The present invention has been described above with reference to the embodiments and examples thereof, but the present invention is not limited to these embodiments and examples and can be modified in various ways.
Claims
1. In mass percent, 10%<Co≦20%, 0.1%≦Si≦2.0%, 0.1%≦Al≦2.0% Contains The balance is a rolled material of an alloy containing Fe and unavoidable impurities, On the rolled surface after magnetic annealing, The value of A obtained by the following formulas (1) and (2) is less than 32°, A soft magnetic material having an area ratio of less than 20% of a region having a crystal orientation within 10° of the {411}<148> orientation. [0010] Here, g indicates an arbitrary crystal orientation, θ indicates an arbitrary direction in the rolling surface, and A θ (g) is the minimum angle between the <100> direction and the direction θ in crystal orientation g, and f(g) is the orientation distribution function.
2. 2. The soft magnetic material according to claim 1, wherein the content of each element contained as the unavoidable impurities is controlled to be within the following range in mass %: C≦0.020%, Mn≦0.10%, P≦0.010%, S≦0.005%, Cu≦0.05%, Ni≦0.10%, Cr≦0.10%, Mo≦0.10%, Ti≦0.010%, O≦0.005%, N≦0.005%.
3. Further, in mass%, 0%<V≦2.0%, 0%<Cr≦2.0% The soft magnetic material according to claim 1 , comprising at least one of the following:
4. 4. The soft magnetic material according to claim 1, wherein the crystal grain size on the rolled surface after magnetic annealing is 30 μm or more and 100 μm or less.
Citation Information
Patent Citations
Iron-cobalt alloy, especially for moving cores of electromagnetic actuators, and method for producing same
JP2004515644A
Ultra-low cobalt iron-cobalt magnetic alloys
JP2017002395A